2013
DOI: 10.1111/jog.12155
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic prevalence of human papillomavirus infection during normal pregnancy: A cross‐sectional study

Abstract: The second trimester may be the most vulnerable period in high-risk HPV infections, which necessitates future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
3
8
2
Order By: Relevance
“…The most common and important neoplastic driver of the lower uterine tract, human papillomavirus (HPV), 1 has been detected in the uterine cervix of 15-25% of pregnant women [2][3][4][5][6] and a cervical HPV infection during pregnancy has been associated with a higher incidence of spontaneous abortions, [7][8][9] premature rupture of the membranes, 10 spontaneous preterm labor, 11,12 pre-eclampsia, 13 and placental 'villitis' not otherwise specified. 12 HPV DNA has been detected in the placenta and amniotic fluid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common and important neoplastic driver of the lower uterine tract, human papillomavirus (HPV), 1 has been detected in the uterine cervix of 15-25% of pregnant women [2][3][4][5][6] and a cervical HPV infection during pregnancy has been associated with a higher incidence of spontaneous abortions, [7][8][9] premature rupture of the membranes, 10 spontaneous preterm labor, 11,12 pre-eclampsia, 13 and placental 'villitis' not otherwise specified. 12 HPV DNA has been detected in the placenta and amniotic fluid.…”
mentioning
confidence: 99%
“…12 HPV DNA has been detected in the placenta and amniotic fluid. 7,11,[14][15][16][17] HPV strains 6,11,16,18, and 31 have been shown to replicate in trophoblast cell lines, [18][19][20] where HPV infection decreased trophoblast number and trophoblast-endometrial cell adhesion in vitro. 19,20 We investigated for the presence of HPV in the placenta and carried out a histopathological and molecular cross-sectional study of 339 placentae from complicated and uncomplicated pregnancies.…”
mentioning
confidence: 99%
“…No difference in HPV clearance was found between the two groups. From cervical swabs obtained from 960 women in each trimester and postpartum, Kim et al [10] found a significantly higher prevalence of HPV and HR-HPV in the second trimester of pregnancy. The effect of a second pregnancy on maternal carriage and outcome of HR-HPV was assessed prospectively as part of the Finnish Family HPV Study [11].…”
Section: Hpv In Pregnant and Non-pregnant Womenmentioning
confidence: 97%
“…Genital warts, which in 90% of cases are caused by HPV-6 and 11, can cause both physical and psychological morbidity for infected individuals [6]. In addition, HPV may informahealthcare.com 10 have a causative role in many cancers of the head and neck (mainly tonsilar) in which HPV-16 is the most prevalent serotype [7]. While the oncogenic potential of some serotypes of HPV is well recognized, the possible role of HPV in pregnancy remains uncertain and requires further investigation.…”
Section: Aims Of Vaccinationmentioning
confidence: 99%
“…2 Malignant transformation appears to require the presence of additional cofactors such as pregnancy, smoking and immunosuppression. 3 Whether pregnancy predisposes to HPV infection and/or malignant transformation is not known. A number of investigators have proposed that the physiological and hormonal changes in pregnancy may modulate immune function leading to changes in the behavior of HPV infection.…”
Section: Introductionmentioning
confidence: 99%